'When creativity gets you fired—why professionals tasked with innovation employ subversion when facing competing institutional demands in hybrid organizations'. Issue 2 (9th February 2022) - Vogelgsang, Lukas
Abstract: How can professionals tasked with innovation navigate institutional complexity in hybrid organizations without contesting the various institutionalized expectations about what constitutes appropriate and beneficial new ideas? This article investigates this question through an ethnographic study of pharmaceutical professionals tasked with research and development at an internationally operating life science company producing pharmaceutical innovations. There, pharmaceutical professionals must address and satisfy three institutional demands to project legitimacy of their new ideas: (1) scientific validity expected by leading members of their profession; (2) commercial value demanded by management; and (3) legal responsibility enforced by state agencies. Facing the challenge of creating legitimate novelty opposite these competing institutional demands, the pharmaceutical professionals initially design new ideas to primarily meet the jurisdictional control exerted by key opinion leaders in the field of clinical pharmacology. Yet, the resultant scientifically tailored designs regularly conflict with the institutional demands enforced by other powerful institutional referents within their organization. To resolve this issue, the professionals utilize a strategy of subversion to undermine the power and authority of these powerful referents by employing tactics of withdraw, manipulation, collusion, and ambushing. Based on these findings, the present study contributes to institutional theory and to literature on creativity and innovation management by theorizing subversive ingenuity as a distinct strategy professionals employ to navigate competing institutional demands during innovation processes in hybrid organizations.